SECOND RECORD OF BLUE-NOSED GRUBFISH, Parapercis albogutta (GÜNTHER, 1872) (PERCIFORMES: PENGUIPEDIDAE) FROM BITUNG, NORTH SULAWESI - Teguh, Teguh; Achmad, Fasmi (UI Scholars Hub, 2009)
A specimens of Blue-nosed Grubfish, Parapercis alboguttata (Günther, 1872) were collected from reef flat of Ron Bolaan, Lembeh Island, North Sulawesi on 21 July 2008. It was caught by hook and line from a depths of about 10 - 20 m. First record of this specimen found in Makassar Strait and deposited at the Bishop Museum (BPBM) in Honolulu, USA. P. alboguttata has been found in many scattered locations in the Indo-West Pacific, from north western Australia, Indonesia, Philippines, Singapore, Malaysia, Oman and Somalia. Morphological features of the Indonesian specimen are reported.